Roadmap to Achieving Sustainable Development via Green Hydrogen - Farah Mneimneh; Hasan Ghazzawi; Mohammad Abu Hejjeh; Matteo Manganelli; Seeram Ramakrishna (Energies, 2023)
The conversion to renewable energy can be achieved when cities and communities start to depend on sustainable resources capable of providing for the basic needs of the community, along with a reduction in the daily problems and issues that people face. These issues, such as poverty, hunger, sanitation, and economic difficulties are highlighted in the Sustainable Development Goals (SDGs), which aim to limit and eradicate these problems along with other environmental obstacles including climate change and Greenhouse Gases (GHGs). These SDGs, containing 17 goals target each sector and provide propositions to solve such devastating problems. Hydrogen contributes to the targets of these sustainable developments, since through its implementation in different industries the levels of GHG will drop and thus contribute to the climate change which Earth is facing. Further, through the usage of such resources, many job opportunities will also be developed, thus enhancing the economy, and lifting the status of society. This paper classifies the four different types of hydrogen and outlines the differences between them. The paper then emphasizes the importance of green hydrogen use within the shipping industry, transportation, and infrastructure, along with economic and social development through job opportunities. Furthermore, this paper provides case studies tackling green hydrogen status in the United Kingdom, United States of America, and European Union as well as Africa, United Arab of Emirates, and Asia. Finally, challenges and recommendations concerning the green hydrogen industry are addressed. This paper aims to relate the use of green hydrogen to the direct and indirect goals of SDG.